Down‐regulation of long non‐coding RNA MEG3 promotes Schwann cell proliferation and migration and repairs sciatic nerve injury in rats - Ma, Yongbin (J Cell Mol Med, 2020)
Peripheral nerve injury and regeneration are complex processes and involve multiple molecular and signalling components. However, the involvement of long non‐coding RNA (lncRNA) in this process is not fully clarified. In this study, we evaluated the expression of the lncRNA maternally expressed gene 3 (MEG3) in rats after sciatic nerve transection and explored its potential mechanisms. The expression of lncRNA MEG3 was up‐regulated following sciatic nerve injury and observed in Schwann cells (SCs). The down‐regulation of lncRNA MEG3 in SCs enhanced the proliferation and migration of SCs via the PTEN/PI3K/AKT pathway. The silencing of lncRNA MEG3 promoted the migration of SCs and axon outgrowth in rats after sciatic nerve transection and facilitated rat nerve regeneration and functional recovery. Our findings indicated that lncRNA MEG3 may be involved in nerve injury and injured nerve regeneration in rats with sciatic nerve defects by regulating the proliferation and migration of SCs. This gene may provide a potential therapeutic target for improving peripheral nerve injury.